Colistin monotherapy or combination for the treatment of bloodstream infection caused by Klebsiella pneumoniae: a systematic review and meta-analysis - Tao Wang; Hongcheng Liu; Huiqing Huang; Yuesong Weng; Xiaojun Wang (BMC Infectious Diseases, 2024)
Abstract Background Bloodstream infection of Klebsiella pneumoniae (BSI-KP) were associated with increased mortality. Klebsiella pneumoniae was tested to susceptible to colistin by E-test and broth microdilution method in clinical laboratory. This study aimed to assess the efficacy of colistin versus tigecycline, carbapenem monotherapy and combination in the treatment of BSI-KP. Methods Electronic databases such as PubMed, Web of Science and Embase were searched. The last search was in November 24th, 2022, addressing the colistin, carbapenems and tigecycline monotherapy and combination treatments in patients with BSI-KP. The primary outcomes were 30-day or 28-day mortality. OR where available with 95% CI were pooled in random-effects meta-analysis. Results Following the outlined search strategy, a total of 658 articles were identified from the initial database searching. Six studies, 17 comparisons were included. However, they all were observational design, lacking high-quality randomized controlled trials (RCTs). Moderate or low-quality evidences suggested that colistin monotherapy was associated with an OR = 1.35 (95% CI = 0.62–2.97, P = 0.45, Tau 2  = 0.00, I 2  = 0%) compared with tigecycline monotherapy, OR = 0.81 (95% CI = 0.27–2.45, P = 0.71, Tau 2  = 0.00, I 2  = 0%) compared with carbapenem monotherapy. Compared with combination with tigecycline or carbapenem, Colistin monotherapy resulted in OR of 3.07 (95% CI = 1.34–7.04, P = 0.008, Tau 2  = 0.00, I 2  = 0%) and 0.98 (95%CI = 0.29–3.31, P = 0.98, Tau 2  = 0.00, I 2  = 0% ), respectively. Conclusions Colistin, carbapenem and tigecycline monotherapy showed similar treatment effects in patients who suffered from BSI-KP. Compared with colistin monotherapy, colistin combined tigecycline therapy might play the synergism effects. Trial registration retrospectively registered.